Primary school staff’s understanding and perceptions of their own and the school role in meeting the social, emotional and mental health (SEMH) needs of all pupils: a grounded theory exploration - Corradi, Olivia (2019)
Within the UK, awareness and concern regarding the importance of children and young people’s (CYP’s) social, emotional and mental health (SEMH) has gained momentum (DfE, 2015; DoH & DfE, 2017; The Guardian, 2017). Government policy emphasises the statutory role that school professionals have in promoting CYP’s SEMH, with the importance of a whole-school approach stressed (DoH & DfE, 2017). Whilst literature related to school staff’s views of issues relating to pupil SEMH is apparent, few studies have been focused on primary schools within the UK. Furthermore, they have failed to sample a range of staff roles. The present study aims to extend understanding and the evidence base through exploration of a range of primary school staff’s perceptions of their own and the school’s role in relation to all pupils’ SEMH, while in turn aiming to provide practice implications for schools and educational psychologists (EPs) and help inform development at a wider level. The study employs constructivist grounded theory methodology, as guided by Charmaz (2014). Data was gathered through semi-structured interview with six members of primary school staff, who each had different roles. Data analysis followed processes advocated by Charmaz (2014), with theoretical sensitisation of outcomes facilitated through a focused review of literature. Through consideration of literature in organisational culture, theories of identity, social constructionism and organisational learning, a theoretical framework from grounded findings is provided. The grounded theory focuses on school ethos, culture and values as underpinning and perpetuating all actions and processes within schools that relate to how school staff engage with and promote pupil SEMH. The constructed framework also integrates notions of identities as educators, organisational growth, and adaption to challenge, change and demands and perceives communication as an integral, multi-functional tool. Insight provides implications for the professional practice of EPs and insight in relation to development within the local context of the local authority (LA). Limitations of the study are acknowledged, and recommendations for further research to address these are presented.